2019
DOI: 10.1002/ldr.3249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the successive planting of Eucalyptus urophylla on soil bacterial and fungal community structure, diversity, microbial biomass, and enzyme activity

Abstract: Eucalyptus are a widely used short‐rotation species for timber production in South China. There are growing concerns regarding the influences of successive planting of Eucalyptus urophylla on microorganisms and soil. The aim of this work was to determine the effects of the successive planting of E. urophylla on soil characteristics. Five different stands, including 5‐, 10‐, 15‐, and 18‐year‐old E. urophylla plantations (abbreviated as 5yr, 10yr, 15yr, and 18yr, respectively) and one native evergreen broadleaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 54 publications
6
69
1
Order By: Relevance
“…A previous study showed no difference in soil bacterial Shannon diversity between Rubber and Eucalypts plantations either in dry season or in wet seasons [37], which was partly in disagreement with our results. Perhaps the difference in plantation age between the previous and this study contribute to this controversial result, since the diversity of soil microbial communities varied substantially with the succession of Eucalypts plantations [36]. The fungal Shannon diversity, however, was significantly lower in EP than in RP, regardless of plantation age.…”
Section: Microbial α-Diversity and Structure And Relationships To Soicontrasting
confidence: 56%
See 1 more Smart Citation
“…A previous study showed no difference in soil bacterial Shannon diversity between Rubber and Eucalypts plantations either in dry season or in wet seasons [37], which was partly in disagreement with our results. Perhaps the difference in plantation age between the previous and this study contribute to this controversial result, since the diversity of soil microbial communities varied substantially with the succession of Eucalypts plantations [36]. The fungal Shannon diversity, however, was significantly lower in EP than in RP, regardless of plantation age.…”
Section: Microbial α-Diversity and Structure And Relationships To Soicontrasting
confidence: 56%
“…According to Li et al [35], soil pH and P are also important in driving soil bacterial composition changes after conversion of forest to Eucalypt plantations. Another study evidenced that soil microbial variation along with the succession of Eucalypt plantations was shaped by the combination of various soil properties (e.g., pH, organic mature, nitrogen, P and potassium) [36]. Recent studies from Lan et al [37,38] suggested that the effects of seasonal changes on soil microbial community overwhelmed the effects of forest conversions, which could explain a large part (31.9%) of the total bacterial composition variance in both plantations and natural forests.…”
Section: Introductionmentioning
confidence: 99%
“…Abandoned farmland can sustain secondary succession (passive restoration) or afforestation (active restoration), leading to a mosaic of reconstructed vegetation and artificial forests (Nadal‐Romero et al, ). The passive and active restoration strategies could reshape the function of an ecosystem and its edaphic properties but also drive variations in soil microorganisms (Glenn, Jordan, & Waugh, ; Jiao et al, ; Lozano et al, ; Zhu, Wang, Chen, Li, & Wu, ). Denitrifying microorganisms are extensive in soil, accounting for approximately 0.5–5% of the total microorganisms (Levy‐Booth, Prescott, & Grayston, ).…”
Section: Introductionmentioning
confidence: 99%
“…The diversity and composition of the bacterial and fungal communities were determined using DNA extraction and Illumina sequencing of 16S rRNA and ITS genes (Yang et al, 2018;Zhu et al, 2019). Soil DNA from the samples wes extracted using MoBio PowerSoilTM DNA Isolation Kits (MoBio Laboratories, Carlsbad, CA, USA) following the manufacturer's instructions and were then stored at −80 C for further process.…”
Section: Soil Microbial Communitymentioning
confidence: 99%
“…The diversity and composition of soil microbial communities vary widely across temporal and spatial scales in terrestrial ecosystems. Many biotic and abiotic factors affect the soil microbial community, including soil pH (Cui, Wang, Xu, Xu, & Xu, 2017;Delgado-Baquerizo, Oliverio, et al, 2018;Lauber, Hamady, Knight, & Fierer, 2009;Lucas-Borja et al, 2012;Tripathi et al, 2013), soil organic carbon (Li et al, 2018), soil nitrogen, phosphorus, and potassium (Liu, Jin, et al, 2019;Zhu, Wang, Chen, Li, & Wu, 2019), the soil C:N ratio (Nakayama et al, 2019;Wang et al, 2015), soil moisture (Xue, Ren, Li, Leng, & Yao, 2017), climate (Delgado-Baquerizo et al, 2016;Jing et al, 2015), and aboveground vegetation traits (e.g., plant cover and diversity) (Delgado-Baquerizo et al, 2019;Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%